A SYSTEMIC FACTOR OF INCREASING THE QUALITY OF HIGHER EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article is devoted to the problems of interaction between the systems of quality assurance and control, management and improvement of professional training. The conditions for the development and implementation of an intra-university quality system, the modern requirements of the international standard and the corresponding plan for the implementation of a quality management system in the university are analyzed.The article discusses the main changes in the system of vocational education, the features of the state-public system of education management, the quality factors of professional training of specialists.